THE EFFECT OF APPLYING LIQUID ORGANIC FERTILIZER FROM FISH WASTE AND GOAT DUNG ON THE GROWTH AND PRODUCTION OF SWEET CORN (Zea Mays Saccaharata L) - Syarifah Mayly; Nurliana Pulungan; Nurhayati; Shampazuraini Samsuri (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study aims to determine the effect of liquid organic fertilizer (POC) from fish waste and goat manure on the growth and production of sweet corn (Zea mays saccharata L.). The study was conducted using a Factorial Randomized Block Design (RAK) with two factors, namely the dose of fish waste POC (0, 100, 200, and 300 ml/plot) and the dose of goat manure fertilizer (0, 1280, 2560, and 3840 g/plot). The parameters observed included plant height, number of leaves, and cob weight per plot. The results showed that the application of fish waste POC and goat manure fertilizer had a very significant effect on the growth and production of sweet corn. The highest dose of fish waste POC (300 ml/plot) and goat manure (3840 g/plot) gave the best results with a plant height reaching 93.47 cm, the number of leaves 16.17 strands, and cob weight per plot of 3561.67 grams. However, the interaction between the two types of fertilizer did not show a significant effect. In conclusion, the use of liquid organic fertilizer from fish waste and goat manure separately can significantly increase the growth and yield of sweet corn.